Integrating Social Solidarity and Contextual Pedagogy: A Socio-Community-Based Model of Inclusive Education in Indonesia’s 3T Regions - Fuad Hilmi; Ina Maryana (International Journal on Education Issues, 2025)
Purpose - This study aims to identify effective strategies for implementing inclusive education based on socio-community participation in Frontier, Outermost, and Disadvantaged (3T) regions of Indonesia. Design/Methodology/Approach - Using a qualitative descriptive design with a case study approach, data were collected through participatory observation, semi-structured interviews, and documentation involving teachers, students, school principals, and parents at SDN 05 Saribakti, SMP IT Darul Hikam, and MA Al-Bayyinah, Peundeuy District, Garut Regency. The data were analyzed using Miles and Huberman’s triangulation model. Findings - The findings reveal that inclusive education in 3T areas can be effectively implemented through collaboration between schools, communities, and local governments by emphasizing local wisdom, collective solidarity, and contextual learning. Social strategies such as gotong royong (mutual cooperation), community mentoring, and faith-based engagement strengthen educational inclusivity and student participation. The study also identifies key challenges, including limited infrastructure, conservative community attitudes, and disparities in teacher quality. Originality/Value - The originality of this study lies in integrating Durkheim’s theory of social solidarity with the Contextual Teaching and Learning (CTL) approach to develop a culturally adaptive model of inclusive education. This integration not only enhances educational access but also promotes social empowerment and sustainable community development in marginalized regions.